PEMBELAJARAN MATEMATIKA MATERI BANGUN DATAR MENGGUNAKAN METODE PERMAINAN TRADISIONAL (ENGKLEK) - Putri Alifatulhaq, Salwa; Saleh, Asmiranti; Az Zahra, Siti Fatimah; Chasanah, Iflahathul (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
The curriculum at the madrasah ibtidaiyah level has many subjects taught in the classroom learning process, one of which is learning mathematics which is the main lesson in the madrasah ibtidaiyah level curriculum, this mathematics learning requires students to be active and easy to understand the material being studied so that educators must provide the material with appropriate methods. fun so that students can easily understand the material being taught. One way is to use traditional game methods, this game method is fun and makes children happy in the learning process so that students can understand difficult material easily. This research aims to describe how the traditional engklek game plays in mathematics learning about flat figures. The method used in this research is qualitative descriptive literature study. The results and discussion of the traditional game method make students active and creative in learning mathematics about flat shapes, they will easily understand the material.